A Subjective Poverty Approach as an Alternative Measurement in Identifying the Poor and Needy - Azhana Othman; Abd Halim Mohd Noor; Mohamed Saladin Abdul Rasool (International Journal of Zakat, 2018)
Poverty can be measured directly (based on consumption) or indirectly (based on income). Both direct and indirect poverty measurement are called objective poverty measurement. Nonetheless, these indicators are not enough capture the multiple aspects of poverty. Therefore, the alternative measure of poverty is needed. Subjective poverty is an individual assessment of their own poverty status. The poor have their own understanding and interpretation of their socio-economic situation. Poverty could be analyzed in a more comprehensive and better dimension by combining objective and subjective measures in identifying the poor. The Millennium Development Goals Report (MDGR, 2015) designates that Malaysia has been successful eliminated objective poverty. Despite that, the issue of poverty still surfing especially the zakat authorities are experiencing increasing in the zakat applications categorized poor and needy each day. To avoid the situation where individuals are wrongly defined as poor or non-poor are to compile objective and subjective measures on poverty. The objectives of the study are to determine the criteria of subjective poor and to propose subjective poverty index (SPI) as an alternative poverty measurement. The empirical analysis was based of 507 zakat applicants of poor and needy in Melaka. The data was analysed using qualitative and quantitative methods in four phases of analysis. The findings confirmed that subjective poverty index (SPI) is an initial effort to explain poverty in the perspective of the poor.